Experimental Evidence on the Relationship between Tax Evasion Opportunities and Labor Supply - Philipp Doerrenberg; Denvil Duncan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Motivated by the observation that access to evasion opportunities is dis- tributed heterogeneously across the labor market, this paper examines the extent to which labor supply elasticities with respect to tax rates depend on such evasion opportunities. We rst discuss the channels through which ac- cess to evasion a ects labor supply responses and then set up a laboratory experiment in which all participants undertake a real-e ort task over several rounds. Subjects face a tax rate, which varies across rounds and are required to pay taxes on earned income. The treatment group is given the opportunity to underreport income while the control group is not. We nd that partici- pants in the treatment group respond di erently to changes in the net-of-tax rate than participants in the control group.
Keywords: H21; H24; J22; 330